Tyrosine 315 determines optimal recruitment of ZAP-70 to the T cell antigen receptor. - Di Bartolo, V; Malissen, M; Dufour, E; Sechet, E; Malissen, B; Acuto, O (2002)
Recruitment of ZAP-70 protein tyrosine kinase to the T cell antigen receptor (TCR) is mediated by the binding of the SH2 domains of this enzyme to phosphorylated ITAM motifs in the CD3 and TCRzeta subunits. We have previously shown that the efficiency of both positive and negative thymocyte selection was decreased in knock-in mice expressing ZAP-70 mutated at Tyr315 (ZAP-70-Y315F), a residue laying in the interdomain B of this protein. Surprisingly, in these cells the amount of phosphorylated TCRzeta chain co-precipitating with ZAP-70-Y315F was significantly reduced compared to control mice. We report now that the binding affinity of ZAP-70-Y315F to phosphorylated ITAM is reduced as compared to the wild-type protein, whereas the intrinsic catalytic activity is untouched. Consequently, phosphorylated ITAM appear to be more accessible to protein tyrosine phosphatases (PTP) and can be readily dephosphorylated. We provide evidence suggesting that the defective ITAM binding induced by Tyr315 mutation is independent of the putative role of this residue as a binding site for Vav-1. Finally, we found that the extracellular signal-regulated kinase pathway is impaired in ZAP-70-Y315F-expressing mice. Collectively, these results demonstrate that Tyr315 has an unsuspected structural role in ZAP-70 and may allosterically regulate the function of the nearby SH2 domains.